2020
DOI: 10.1177/1073110520979386
|View full text |Cite
|
Sign up to set email alerts
|

Legal and Ethical Analysis of Advertising for Elective Egg Freezing

Abstract: This paper reviews common advertising claims by egg freezing companies and evaluates the medical evidence behind those claims. It then surveys legal standards for truth in advertising, including FTC and FDA regulations and the First Amendment right to free speech. Professional standards for medical advertising, such as guidelines published by the American Society for Reproductive Medicine (AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
(44 reference statements)
0
1
0
4
Order By: Relevance
“…31,32 However, media information is often limited and information on fertility clinic websites have been rated as low quality and strongly biased towards EEF. 12,27,30,[33][34][35][36][37][38] Women who have previously frozen eggs have reported that their greatest desire was to have detailed EEF information, focusing specifically on women. 23 To address this, we developed an online Decision Aid (DA) for women considering EEF.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 However, media information is often limited and information on fertility clinic websites have been rated as low quality and strongly biased towards EEF. 12,27,30,[33][34][35][36][37][38] Women who have previously frozen eggs have reported that their greatest desire was to have detailed EEF information, focusing specifically on women. 23 To address this, we developed an online Decision Aid (DA) for women considering EEF.…”
Section: Introductionmentioning
confidence: 99%
“…A fim de promover a expansão do debate público sobre o tema, o autor o apresenta de um modo mais acessível a indivíduos não especialistas. Com uma escrita fluida, que facilita a compreensão sobre tópicos complexos, Araujo (2019) divide a obra em três grandes áreas: inteligência artificial (IA), genética e biotecnologia e aprimoramento humano.…”
unclassified
“…Dentre eles, destacamos um exemplo dado pelo autor. Segundo Araujo (2019,13) O exemplo acima ilustra a dimensão dos desafios que estão diante de nós. 4 Por um lado, há a questão sobre se devemos permitir e investir na possibilidade de que seres humanos, no exercício de certas funções profissionais tão relevantes para o funcionamento do ordenamento jurídico de uma sociedade democrática, sejam substituídos, ainda que parcialmente, por sistemas não humanos que, até o presente momento, não respondem a ninguém (no sentido de prestação de contas), não podendo ser responsabilizados profissional, etica ou juridicamente.…”
unclassified
See 2 more Smart Citations